2013
DOI: 10.1016/j.aquatox.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tris(1,3-dichloro-2-propyl) phosphate and triphenyl phosphate on receptor-associated mRNA expression in zebrafish embryos/larvae

Abstract: a b s t r a c tTris(1,3-dichloro-2-propyl) phosphate (TDCPP) and triphenyl phosphate (TPP) are frequently detected in biota, including fish. However, knowledge of the toxicological and molecular effects of these currently used flame retardants is limited. In the present study, an in vivo screening approach was developed to evaluate effects of TDCPP and TPP on developmental endpoints and receptor-associated expression of mRNA in zebrafish embryos/larvae. Exposure to TDCPP or TPP resulted in significantly smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 55 publications
8
93
3
Order By: Relevance
“…The result of the TDCPP agonistic activity towards the TR was consistent with those of several previously reported in vivo studies, which demonstrated that exposure to TDCPP could up-regulate the transcription of TR mediated genes in zebrafish embryos/larvae (Liu et al, 2013a;Wang et al, 2013). However, our results were different from those of a previously reported in vitro study, which showed that several OPEs, including TDCPP, had no TR activity (Kojima et al, 2013).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The result of the TDCPP agonistic activity towards the TR was consistent with those of several previously reported in vivo studies, which demonstrated that exposure to TDCPP could up-regulate the transcription of TR mediated genes in zebrafish embryos/larvae (Liu et al, 2013a;Wang et al, 2013). However, our results were different from those of a previously reported in vitro study, which showed that several OPEs, including TDCPP, had no TR activity (Kojima et al, 2013).…”
Section: Discussioncontrasting
confidence: 56%
“…Wang et al (2013Wang et al ( , 2015aWang et al ( , 2015b found that TDCPP changed TH levels and altered the transcription of genes involved in the hypothalamic-pituitary-thyroid (HPT) axis in zebrafish embryos/larvae. Liu et al (2013a) evaluated the effects of TDCPP and TPP on six receptor-associated expression of mRNA in zebrafish embryos/ larvae, and the results showed that TH receptor-centered gene networks were altered by OPEs. Using real-time reverse transcription-PCR, it has been demonstrated that exposure to TDCPP and TCPP altered the mRNA abundance of genes associated with the TR pathway in cultured hepatocytes and neuronal cells derived from embryonic chickens (Crump et al, 2012;Farhat et al, 2013).…”
Section: J O U R N a L O F E N V I R O N M E N T A L S C I E N C E Smentioning
confidence: 99%
“…Previous studies have demonstrated that several OP esters cause developmental toxicity and endocrine disruption in vivo and in vitro (Crump et al, 2012;Dishaw et al, 2012;Farhat et al, 2013;Fu et al, 2013;Liu et al, 2012bLiu et al, , 2013McGee et al, 2012McGee et al, , 2013Wang et al, 2013). For example, exposure of zebrafish embryos to tris(1,3-dichloro-2-propyl) phosphate (TDCPP) disrupted embryogenesis and caused larval malformation, with median lethal concentrations (LC 50 ) ranging from 3.7 to 7.0 mg/L (Fu et al, 2013;Liu et al, 2013;McGee et al, 2012;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, exposure of zebrafish embryos to tris(1,3-dichloro-2-propyl) phosphate (TDCPP) disrupted embryogenesis and caused larval malformation, with median lethal concentrations (LC 50 ) ranging from 3.7 to 7.0 mg/L (Fu et al, 2013;Liu et al, 2013;McGee et al, 2012;Wang et al, 2013). In chicken embryos, Farhat et al (2013) reported that injection of TDCPP or tris(1-chloro-2-propyl) phosphate (TCPP) delayed pipping, reduced tarsus length, and changed hormone concentrations and mRNA levels included in xenobiotic metabolism and thyroid hormone pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro reporter gene assays showed that TDCPP has potential endocrine-disrupting effects and can act as an androgen receptor (AR) antagonist (Kojima et al, 2013 (McGee et al, 2012;Fu et al, 2013;Liu et al, 2013a), including thyroid endocrine-disruption activity, as it reduced the levels of circulating T4 levels in zebrafish larvae (Wang et al, 2013). Moreover, in cultured chicken embryos TDCPP caused altered expression of TH-responsive genes (Crump et al, 2012;Farhat et al, 2013).…”
Section: Introductionmentioning
confidence: 99%